The Role of Teacher Identity on Using Formative Assessment to Support the Learning of Students with ASC in Mainstream Classes - Aslantas, Sercan (2023)
At the centre of this study is the question of the role of teacher identity in how formative assessment (FA) methods are used to support the learning of students with Autism Spectrum Conditions (ASC) in mainstream classes. To address this question, a qualitative case study was conducted with 6 teachers, 6 teaching assistants and 4 students with ASC in two primary mainstream schools in England. In this case study, interviews, observations and documents were used as the data collection method, and consequently, the thematic inductive analysis method was employed in the analysis of the data. Findings suggest that teacher identity is influenced by three main factors, and these factors directly and indirectly affect teachers' formative assessment practices while teaching students with ASC. The first category is personal factors; teachers are influenced by their biography, emotions, self-esteem and role conflict in forming their teacher identities. The second category is contextual factors that relate to policy, school context and school leadership and are part of school culture. These factors significantly affect and shape teachers' pedagogy and assessment practices. The last category is professional factors, including teaching experience, collaborations, pedagogical content knowledge, curriculum and assessment. From these findings, it is understood that teachers and teaching assistants recognise the importance of inclusive education and the use of formative assessment, and despite the many difficulties they encounter, teachers and TAs support the education of students with ASC in mainstream settings. Teachers consider formative assessment to be a flexible and effective way to reach the student with ASC and follow the learning journey. Overall, this study demonstrates why teachers use formative assessment, the link between their identity and formative assessment, and how students with ASC respond to these methods. For this reason, the research findings are important in suggesting that teachers and teacher assistants should develop awareness of the power of their identity, inform parents about their supporting roles in the assessment process, inform the school leaders of how to prepare a more confident learning and teaching environment for teachers and students, and lastly, give an idea to policy makers about preparing an assessment policy that should include detailed information about formative assessment in a mainstream environment.